Das Manövrieren inmitten der zahlreichen Wendepunkte der STS - Julio Paulos; Loïc Riom (Revue d'anthropologie des connaissances)
This paper speculates on what it's like to write a call for papers for an international conference. From behind the scenes, it aims to reflect on the singular exercise of addressing a community of colleagues around a particular discipline and/or a particular topic. The question of material fragility - to which this call was dedicated - is considered from this point of view, that is, not in a conceptual or methodological manner, but from a practical research experience. In the form of an epistolary exchange, the text gives an account of the way in which a “turn” or disciplinary moment engages, provokes and orients ways of doing and thinking about research.